(untitled) (REVISTA NODO, 2015)
Complexity represents a paradigm to address the problems of a substantial number of interrelated nonlinearly variables as an organic whole, to what has been called problems of "organized complexity" (Weaver, 1948). This paradigm is making its way to read the city as a system of organized complexity, through the "new science of cities" named after Batty´s last publications. This paper summarize the evolution of the paradigm of complexity, describes the progress of the study of the city through complexity, and the methods used in the new science of cities based on a review of the literature to date. It propounds new directions for future research, particularly the need to study the learning capacity of the city in its urban management.